1998
DOI: 10.1023/a:1020599209468
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Cytochrome c oxidase from bovine heart contains seven high-affinity binding sites for ATP or ADP and three additional only for ADP. One binding site for ATP or ADP, located at the matrix-oriented domain of the heart-type subunit VIaH, increases the H+/e- stoichiometry of the enzyme from heart or skeletal muscle from 0.5 to 1.0 when bound ATP is exchanged by ADP. Two further binding sites for ATP or ADP, located at the cytosolic and the matrix domain of subunit IV, increases the K(M) for cytochrome c and inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…On the other hand, the lack of activity in the presence of higher concentrations of cholate may be due to some additional effect. In addition, it has been suggested that ATP, which has a structure similar to cholate, can also associated with the CH2-binding site (17, 34, 35), suggesting that under physiological conditions, solutes such as ATP bind to the protein and regulate its activity.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the lack of activity in the presence of higher concentrations of cholate may be due to some additional effect. In addition, it has been suggested that ATP, which has a structure similar to cholate, can also associated with the CH2-binding site (17, 34, 35), suggesting that under physiological conditions, solutes such as ATP bind to the protein and regulate its activity.…”
Section: Resultsmentioning
confidence: 99%
“…The original suggestion, based on crystallographic 1 and activity 20, 21, 63 studies on the mammalian oxidase, was that the cholate sites in bovC c O represented adenine nucleotide regulatory sites, due to the similar size, shape, and binding characteristics of these ligands. 1 Our current studies do not rule this out, but we did not observe significant effects of adenine nucleotides in the assay systems described here.…”
Section: Discussionmentioning
confidence: 99%
“…It was postulated that the decreased H + /e − ratio for the enzyme from skeletal muscle tissue (subunit VIaH) at high ATP/ADP ratios (e.g. during sleep), and for the enzyme from nonskeletal muscle tissues, participate in thermogenesis 52b, 59…”
Section: High Atp/adp Ratios Decrease the H+/e− Stoichiometry Onlymentioning
confidence: 99%